Condition of Coral Reef in Kelagian Besar Island - Novriadi Novriadi; Khairul Anam; Abdul Aziz (Journal of Science and Applicative Technology, 2023)
The coral reef ecosystem plays many important roles for society. One of the its role is as a tourist attraction. Kelagian Island lies near Pahawang island which is the major attraction of marine tourism in Lampung. This position makes Kelagian Island the most potential alternative island after Pahawang Island. However, sufficient information about the coral condition and profile in Kelagian Island has yet to support this potential. For that reason, a study about coral reef conditions on Kelagian island must be conducted to provide information and support the possibility of tourism development on Kelagian island. This study was conducted in August 2022 using Point Intercept Transect (PIT) in three different sites on Kelagian Island. Coral reef condition in 3 meter depth were generally in good condition, meanwhile in 7 meters depth coral reef condition were in medium state. There were 22 genera found in Kelagian island. Acropora and Porites were found dominating three meter depth. On the other hand in seven meter of depth, Goniopora and Favia were abundantly found. Diversity index, Evenness, and Dominance Index in Kelagian Island are 2,29-2,49 (medium), 1-0,83 (stable), and 0,12-0,15 (low) respectively.